Thermo-mechanical degradation in ABS-Fe3O4 polymer nanocomposite due to repeated electromagnetic heating. (15th November 2020) - Vattathurvalappil, Suhail Hyder; Kundurthi, Saratchandra; Drzal, Lawrence T.; Haq, Mahmoodul
Abstract: The reinforcement of conductive nano-/micro-fillers in thermoplastic polymers allows for rapid heating upon exposure to electromagnetic (EM) radiation. This phenomenon has been used to create reversible adhesives that allow bonding/removal of substrates via controlled EM exposure. This process of repeated heating/cooling can introduce thermal and mechanical degradation, which is not well understood. In this work, ferromagnetic nanoparticles (Fe3 O4 ) were embedded in ABS polymer using melt-processing. The resulting polymers were subjected to EM heating with varying exposure time and multiple heat/cool cycles. TGA and FTIR spectroscopy were conducted to understand the extent of thermomechanical degradation. Tensile and Izod impact tests were performed on samples post EMI exposure and compared with control samples (no EMI exposure) to understand the effects of degradation. Results indicate that prolonged exposure to induction heating reduces the overall mechanical properties of the reversible polymer. However, repeated heating of ABS/Fe3 O4 nanocomposites within the melting temperature only effects the ductility, and is attributed to loss of the toughening agent butadiene. Overall, the study creates a first benchmark for a possible path to control EM heating to prevent thermomechanical degradation of reversible thermoplastics.